Pelatihan Pembuatan Kuis Interaktif Menggunakan Aplikasi Quizizz dan Wordwall Untuk Guru SMP Islam Hidayatul Athfal - Widyah Noviana; Harumi Widihastuti; Sri Wahyuni; Kusumawati (AMMA : Jurnal Pengabdian Masyarakat, 2022)
The purpose of community service is to provide counseling and training regarding the application of learning media that teachers can use to evaluate learning during the Covid-19 pandemic. This community service is carried out at SMP Islam Hidayatul Athfal which is located at Jalan Persahabatan No.9, Cinere Village, Cinere District, Depok City, West Java Province. Methods for implementing community service include: 1) Observation stage, at this stage the PkM implementing team makes observations at schools. The PkM Team asks permission from the school principal, determines the schedule and discusses the facilities to be used, 2) Planning stage, at this stage the PkM Team conducts debriefing and prepares PkM proposals, 3) Preparatory stage, at this stage the PkM Team communicates again with the school to determine number of participants, place and method of training, 4) Implementation stage, at this stage the PkM activities take place, 5) Discussion Stage, at this stage the PkM Team and the teacher conduct a question and answer session, 6) Evaluation Phase, the teacher submits the results of the training to the PkM Team through e-mail. The result of this community service is that SMP Islam Hidayatul Athfal teachers can operate the quizizz and wordwall applications.